Effect of specimen configuration on deterioration of silicone rubber for polymer insulators in salt fog ageing test - Marungsri, B.; Shinokubo, H.; Matsuoka, R.; Kumagai, S. (IEEE transactions on dielectrics and electrical insulation, 2006)
The paper investigates the effects of specimen configuration on the deterioration of silicone rubber insulators in a salt fog ageing test. A cyclic salt fog ageing test was conducted on three types of high-temperature vulcanized silicone rubber (HTV SiR) specimens: two types of insulators having sheds, and plain rods without sheds. The test was based fundamentally on the CIGRE WG 15-04 specifications. After 50 test cycles, the three types of specimens showed different degrees of surface deterioration. Erosion on the straight shed insulator was more severe than that on the alternate shed insulator even though the two had the same leakage distance. No erosion was observed on the rod-type specimens, which had shorter leakage distances than the insulator-type specimens.